Analysis of factors influencing the occurrence of mental emotional disorders (med) among employees at penjaringan primary health center - R. Muh. Ihsan Sasraningrat; Ernyasih Ernyasih; Munaya Fauziah; Rusdi Effendi (Science Midwifery, 2026)
Mental Emotional Disorders (MED) are prevalent among healthcare workers due to excessive workload and occupational stress. This study aimed to analyze factors associated with Mental Emotional Disorders among employees at Penjaringan Primary Health Center, Jakarta. A quantitative cross-sectional study was conducted involving 146 employees selected based on inclusion criteria. Data were collected using questionnaires and the Self Reporting Questionnaire-20 (SRQ-20). Variables analyzed included workload, managerial system, organizational culture, coping mechanism, psychological resilience, mental health history, and well-being. Data were analyzed using chi-square and multiple logistic regression tests. The prevalence of MED was 16.4%. Significant associations were found between workload (p=0.001), organizational culture (p=0.001), coping mechanism (p=0.001), and psychological resilience (p=0.001) with MED incidence. Multivariate analysis identified psychological resilience as the dominant factor associated with MED. The study concludes that excessive workload and low resilience increase the risk of Mental Emotional Disorders among healthcare workers. Organizational interventions focusing on workload management and resilience strengthening are recommended.